SEJARAH EKSPLOITASI MINYAK MINAS PADA TAHUN 1938-1963 - Mardiansyah Pratama Putra; Marwoto Saiman; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Indonesia is one country that is rich in natural resources one of which is petroleum, the oil sector is never apart from the polemic in many countries including Indonesia, which is a country that has oil reserves are abundant, but occurring oil reserves are actually in the "master "by a foreign company in which of the 47 mining area consisting of 25 groups majors (international oil companies are huge), comprising Chevron to 7 working area of operation, Exxon / Mobile with 5 WKP, British Petroleum with 3 WKP, Gulf Resource with 5 WKP , Total / Fina with 2 WKP Petro and other Majors with 3 WKP WKP and the remaining 22 are not classified Majors.1 Indonesia is a country that is very strategic to attract many multinational companies to invest corporation. Indonesia is one of the oldest centers of oil production in the world. So far in 1871 the Dutch had drilled oil seepage areas in an attempt to obtain the filtered oil into light oil. In 1883, a tobacco planter, Aeilko Janszoon Zijlker, obtaining a concession to drill in North Sumatra, which resulted in commercial production. The purpose of this study was to determine the history of the discovery of oil Minas during the Japanese occupation in Indonesia, to determine the Minas oil exploitation during the Japanese occupation in Indonesia, the Japanese government policy To know of the existence of oil Minas, Riau. The method used in this research is qualitative descriptive method with specific historical and documentary. The research location is Minas, Riau. When the study began seminar as from proposal to test the thesis. The technique of collecting data from the sources of books, interviews and documents relavan. The results of this study indicate that Minas is a decent area explored as a local history.Keywords: Exploitation, Oil, Minas